Alzheimer’s disease and COVID-19: Interactions, intrinsic linkages, and the role of immunoinflammatory responses in this process - Li, Wei; Sun, Lin; Yue, Ling; Xiao, Shifu (Frontiers in Immunology, 2023)
Abstract Alzheimer's disease (AD) and COVID-19 share many common risk factors, such as advanced age, complications, APOE genotype, etc. Epidemiological studies have also confirmed the internal relationship between the two diseases. For example, studies have found that AD patients are more likely to suffer from COVID-19, and after infection with COVID-19, AD also has a much higher risk of death than other chronic diseases, and what's more interesting is that the risk of developing AD in the future is significantly higher after infection with COVID-19. Therefore, this review gives a detailed introduction to the internal relationship between Alzheimer's disease and COVID-19 from the perspectives of epidemiology, susceptibility and mortality. At the same time, we focused on the important role of inflammation and immune responses in promoting the onset and death of AD from COVID-19. Keywords: Alzheimer's disease (AD), COVID-19, epidemiological studies, mechanism, inflammation and immune responses